The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4103/atm.atm_151_20
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan intermittent fasting and immunity: An important topic in the era of COVID-19

Abstract: WITH the growing pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome (SARS)-related coronavirus (SARS-CoV-2) infection, a parallel growing interest arose concerning potential preventive and adjunct therapies, dietary and lifestyle modifications, and remedies that may boost the immunity against SARS-CoV-2 infection. Furthermore, as Ramadan intermittent religious fasting that is practiced by about one and a half billion Muslims throughout the globe is coincide this year wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
0
19
0
2
Order By: Relevance
“…Of interest is that diurnal intermittent fasting and its model of Ramadan affect the immunity by changing the body's response toward infection, inflammation, and oxidative stress (23). For instance, Ramadan fasting reduces the pathogenicity of Mycobacterium tuberculosis by increasing the macrophage number and INF-γ secretion in fasting volunteers (23). It was demonstrated to be safe for patients infected with HIV and on antiretroviral therapy (23).…”
Section: Fasting Immunomodulatory Effect In Experimental Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of interest is that diurnal intermittent fasting and its model of Ramadan affect the immunity by changing the body's response toward infection, inflammation, and oxidative stress (23). For instance, Ramadan fasting reduces the pathogenicity of Mycobacterium tuberculosis by increasing the macrophage number and INF-γ secretion in fasting volunteers (23). It was demonstrated to be safe for patients infected with HIV and on antiretroviral therapy (23).…”
Section: Fasting Immunomodulatory Effect In Experimental Studiesmentioning
confidence: 99%
“…It should be noted that the beneficial effects of Ramadan intermittent fasting on immunity might be reduced by the sleep pattern practiced in the blessed month of Ramadan. Several studies showed that total sleep time significantly decreased by about 1 h in Ramadan nights, while daytime sleepiness increased (23,36). Partial sleep deprivation is associated with increased susceptibility to viral infections (23,37).…”
Section: Fasting Potential Favorable Effect Against Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of current treatment for SARS-CoV-2, a strong interest has emerged regarding the optimization of the intake of dietary factors, specifically lipids, to effectively reduce inflammation and oxidative stress, thus strengthening the immune response during the COVID-19 crisis. Besides, metabolic changes accompanied by IF that trigger antiviral mechanism has been suggested elsewhere [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%